2011
DOI: 10.1007/s10120-011-0023-7
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy-assisted subtotal gastrectomy with very small remnant stomach: a novel surgical procedure for selected early gastric cancer in the upper stomach

Abstract: Total gastrectomy or proximal gastrectomy is usually performed either as an open procedure or laparoscopically for the treatment of early gastric cancer (EGC) in the upper stomach. However, quality of life after either total or proximal gastrectomy is not so satisfactory. The authors report a novel surgical procedure, laparoscopyassisted subtotal gastrectomy (LAsTG), by which a very small remnant stomach is preserved, for the surgery of selected EGCs in the upper stomach. Twenty-three patients with EGC in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 21 publications
0
28
1
Order By: Relevance
“…However, an intraperitoneal pressure of 8 mmHg was sometimes selected if a lower cardiopulmonary reserve was expected. A total of five ports (each 5-12 mm) were inserted, and LADG with perigastric and suprapancreatic lymph node dissection was conducted as reported previously [22][23][24][25][26]. Extracorporeal reconstruction was performed using a 4-to 5-cm upper midline incision with Billroth-I reconstruction after LADG.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…However, an intraperitoneal pressure of 8 mmHg was sometimes selected if a lower cardiopulmonary reserve was expected. A total of five ports (each 5-12 mm) were inserted, and LADG with perigastric and suprapancreatic lymph node dissection was conducted as reported previously [22][23][24][25][26]. Extracorporeal reconstruction was performed using a 4-to 5-cm upper midline incision with Billroth-I reconstruction after LADG.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…In this study, the margin size was similar to those reported in previous studies evaluating subtotal The gastric occlusion line (thick black arrows), metal clips (thin black arrow), and the tumor (white arrow) can be seen in the same view when using gastroscopic retroflexion. gastrectomy [16,19] . Although few reports have described the transection time including the time for gastroscopy [14] , we believe the transection achieved using GRREG for TLDG was acceptable and beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…However, the definitive method for gastric transection with a safe cancer margin has not been established fully, especially for patients with early gastric cancer in the middle or upper stomach. Some reports have advocated the usefulness of intraoperative gastroscopy [14][15][16][17][18] with preoperative marking using metal clips. Nevertheless, there are concerns with regard to utilizing the normal gastroscopic forward view.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 However, this procedure is complicated and requires the use of advanced techniques. Conversely, the anastomosis with a circular stapler could be simply placed on the transection line of the minimal remnant stomach, 14,24,25 although the anvil of the circular stapler must be inserted into the small remnant stomach. Kosuga et al used the OrVil for all of their patients.…”
mentioning
confidence: 99%